Singapore : Precautionary Unilateralism : Port State Prohibition on Open-loop Scrubber Discharges and the IMO 2020 Fuel Oil Sulphur Limit - Honniball, Arron N (Brill Nijhoff, 2020)
10.1163/24519391-00402012